Mitigating DDoS Attacks in Cloud Networks (International Journal of Engineering & Extended Technologies Research (IJEETR), 2021)
Distributed Denial of Service (DDoS) attacks represent a significant and growing threat to cloud networks, capable of causing extensive service disruptions and substantial financial and reputational damage. These attacks leverage multiple compromised devices to flood a target with malicious traffic, overwhelming its resources and rendering services unavailable to legitimate users. As cloud computing becomes increasingly integral to business operations, the need for effective DDoS mitigation strategies has never been more critical.This paper delves into the multifaceted nature of DDoS attacks, categorizing them into volumetric, protocol, and application layer attacks, each with distinct characteristics and impacts. It examines the specific vulnerabilities of cloud networks to these attacks, highlighting the unique challenges posed by their distributed and scalable nature.To combat these threats, a multi-layered approach to DDoS mitigation is essential. This includes traffic filtering and rate limiting to control the flow of traffic, anomaly detection and machine learning algorithms to identify and respond to attacks in real-time and leveraging the inherent scalability of cloud infrastructure to absorb and distribute attack traffic. Additionally, the use of Content Delivery Networks (CDNs) and specialized DDoS protection services can provide robust defenses against these attacks.Looking ahead, the paper explores future advancements in DDoS mitigation, emphasizing the potential of AI-driven mitigation tools, blockchain technology for creating decentralized and tamper-proof networks, advanced threat intelligence for proactive defense, and enhanced collaboration between cloud service providers, security vendors, and organizations.By providing a comprehensive understanding of DDoS attacks and the strategies to mitigate them, this research aims to equip organizations with the knowledge and tools necessary to protect their cloud networks. As DDoS attacks continue to evolve, staying ahead of these threats will require continuous innovation and adaptation in mitigation techniques.
Keywords: DDoS; cloud networks; mitigation; traffic filtering; anomaly detection; AI; Blockchain